The effect of ethanol extract of Sarang Semut plant (Hypnophytum formicarum) towards Angiogenesis for wound healing after tooth extraction: Experimental research on Marmot (Cavia cobaya) - Putri, Sartika Amelia; Ismardianita, Efa (Universitas Padjadjaran, 2016)
Introduction: Tooth extraction causing injuries, to accelerate wound healing was given medication. Drugs commonly used for wound healing after tooth extraction is povidone iodine act as bacteriostatic for all germs. Excessive use of povidone iodine can cause side effects such as itching, pain in the area around the wound, swelling and dermatitis, so it sought a safe substitute drugs derived from herbs. One of the herbs are often used by people in the Mentawai Islands is a Sarang Semut's root species of Hypnophytum formicarum. This study was aimed to determine the effect of sarang semut’s extract orally for angiogenesis in wound healing after tooth extraction. Methods: This research was experimental with posttest only control group design. Subjects were 48-animal marmots were divided into 4 groups, will be deprived of his left mandibular insisivus. Group I (control 0,5% CMC, treatment group II, III, IV with 4,65mg, and 9.3 mg 6,2 mg dose tuber ethanol extract dissolved anthill in CMC 0.5%), were given 3 ml orally, 3 times a day until the day of decapitation. Futher histological preprations made by HE staining and the observed area is apex, medial, servical,and lateral used 400x magnification. The data was analyzed with parametric test One-Way ANOVA, and to see the significance between dose used LSD test. Results: The results showed that the extract of sarang semut effect (p<0,05) on the angiogenesis in wound healing after tooth extraction. Conclusion: The most effective concentration was 4,65 mg.